Pengaruh Penggunaan Ekstrak Jahe Merah (Zingiber Officinale Var. Rubrum) Dengan Variasi Tempat Bertengger Terhadap Parameter Hematologi Ayam Broiler - Chandra Wijaya; Syafwan Syafwan; Sarwo Edy Wibowo (CV. SINAR HOWUHOWU, 2026)
This study aimed to determine the effect of administering red ginger extract (*Zingiber officinale* var. *rubrum*) and using a cool perch on heat stress indicators in broiler chickens. The study utilized 198 broiler chickens housed in 18 experimental pens, arranged in a Completely Randomized Design (CRD) consisting of three treatments and six replicates. The treatments were: P1 (control: no red ginger extract and no cool perch), P2 (red ginger extract without a cool perch), and P3 (red ginger extract with a cool perch). The variable observed was the heterophil/lymphocyte (H/L) ratio, an indicator of physiological stress in broilers. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s test via SAS software. The results showed that the treatments had a significant effect (P<0.05) on the broiler H/L ratio. The mean H/L ratio values ​​for the treatments were 0.350 ± 0.080 for P1, 0.198 ± 0.071 for P2, and 0.206 ± 0.065 for P3. Duncan’s post-hoc test indicated that P1 differed significantly from P2 and P3, whereas there was no significant difference between P2 and P3. In conclusion, the administration of red ginger extract—either alone or in combination with a cool perch—is effective in lowering the heterophil/lymphocyte ratio, thereby reducing heat stress levels in broiler chickens.